Docetaxel, bevacizumab, and gemcitabine for very high risk sarcomas in adolescents and young adults: A single‐center experience. Issue 4 (5th November 2016) - Kuo, Christopher; Kent, Paul M.; Logan, Antonio D.; Tamulonis, Karen B.; Dalton, Kristen L.; Batus, Marta; Fernandez, Karen; Mcfall, Rebecca E.
Abstract: Background: Adolescent and young adult (AYA) patients with very high risk sarcomas have poor outcomes and are in need of novel therapies. Procedure: From January 2005 to February 2016, we retrospectively identified all AYA patients with relapsed or metastatic high‐grade sarcomas, who were treated with at least one cycle of docetaxel (T), bevacizumab (A), and gemcitabine (G) (TAG ; T = 100 mg/m 2 Day 8, A = 15 mg/kg Day 1, G = 1, 000 mg/m 2 Days 1 and 8). Results: Fourteen patients, median age of 20 (15–30), received a total of 80 cycles of TAG, and were followed for a median of 83 months. Diagnosis included osteosarcoma (OST; 8), Ewing sarcoma (3), and soft tissue sarcoma (3). Five of 14 patients achieved clinical remission (CR), 3 had partial responses (PR), 3 had stable disease (SD), and 3 had progressive disease (PD). The median progression‐free survival and overall survival were 7 and 19 months, respectively. The objective response rate (CR + PR) and tumor control rate (CR + PR + SD) were 57% and 79%, respectively, with two patients alive after 5 years; toxicities included thrombocytopenia, neutropenia, and capillary leak syndrome. Conclusions: Our study builds on previous studies utilizing TAG in adult leiomyosarcoma (LMS) by focusing on AYA, non‐LMS sarcomas, especially OST. Our experience suggests that TAG is well tolerated and has activity in very high risk sarcomas in AYA.